The Seedling Project - Davidsson, Ella; Johansson, Ida; Edstam, Frida; Zorn, Markus; Gold, Sarah (My University, 2020)
The Seedling Project aims to highlight the value of organ- ic waste and the possibilities of local food production at a household level through online education material suitable for children across the globe. When beginning our project in Kisumu, Kenya, we found there was a need to improve the waste management within the city. Especially the organic waste, being 60 percent of the total waste, caused problems at markets and on the streets. We shifted our focus to children in primary school to find how we could support their learning within the subject of agriculture and composting. By teaching children about the circularity of food, food waste and small-scale farm- ing, we could show the value of organic waste and inspire to sort and make use of it. The Covid-19 pandemic outbreak made us reframe the project. Due to the pandemic, a lot of children were restricted to quarantine and could no longer go to school. This made us shift focus from the context of Kisumu to a global context where we found there was a need for home activities and education. We created manuals for home learning and invited 12 children from Kenya, Austria, Sweden and the U.S. to participate in a pilot project. To educate the children in the pilot group, an online platform was set up where the participants could share their work and comment on each other ́s plants, composts and food, among others. In the manuals the two guiding avatars, Space Potato and Wormy, graphically explained to the children how to do the given task, with the purpose of reducing the language barriers and to make the activities more fun. For future expansion of the project, we collected the learning material and the method we used in a guiding handbook. This was sent out to the parents of the pilot group and to different communities on social media, such as Fridays for Future.